Strengthening nutrition, health, and food security in Nigeria: policy and programming alignment for innovation scaling - Osei-Amponsah, Charity; Gurmu, M.; Twine, E. (International Water Management Institute, 2025)
Nigeria faces a deepening crisis in nutrition, health and food security, driven by high levels of malnutrition, climate vulnerability, poverty, and weak institutional systems. Despite having an extensive set of national policies and programs such as the National Multi-Sectoral Plan of Action for Food and Nutrition (NMPFAN), the Agricultural Sector Food Security and Nutrition Strategy (AFSNS), and the National Agricultural Technology and Innovation Policy (NATIP), implementation remains weak. The report reviews 23 policies and 24 institutional programs, revealing strong aspirational commitments but limited actionable demand. Only a fraction of policies include clear budgets, coordinated implementation plans, or mechanisms for scaling innovations.